Dynamic strength, reinforcing mechanism and damage of ceramic metal composites. (1st October 2022) - Lin, Kuixin; Zeng, Meng; Chen, Hongmei; Tao, Xiaoma; Ouyang, Yifang; Du, Yong; Peng, Qing
Highlights: We fully study the shock responses of ceramic metal composites via NEMD. The interaction of shock-wave with the interface affects dislocation strengthening. An abnormal softening effect is captured under shock loading. The interface possesses negative effect on damage for composites. Abstract: Shock tolerance is desirable for ceramic particles-reinforced metal matrix composites in many applications, where the dislocation dynamics evolution under the extreme load is the key but still elusive. Herein, we have investigated the dislocation motion and interaction under shock loading of SiC/Al nanocomposites using molecular dynamics simulations. We have demonstrated that the plastic deformation occurs at an impact velocity (0.5 km/s) lower than the Hugoniot elastic limit of aluminum due to the reflected shear wave effect. The Al/SiC interfaces act as a dislocation emitter to control dislocation multiplication density and slip direction, opening a new pathway to achieve ultrahigh-strength via shock loading. When the impact velocity (1.0 or 1.5 km/s) exceeds the Hugoniot elastic limit, the effect of nanoparticles on dislocation structure has changed from multiplying to retarding dislocations. The spall strength of composites improves due to dislocations pile-up at interface. Instead, the damage in the matrix is exacerbated, owing to the enhanced residual peak stress and interface reflection waves. In addition, the effect of abnormal shock softening determined by atomic velocity is revealed, which could be suppressed by increasing impact energy dissipation. Meanwhile, dynamic compressive strength depends on pressure and dislocation structures evolution. Our atomistic insights might be helpful in designing advanced shock-tolerant materials. Graphical abstract: Image, graphical abstract